Hydrothermal liquefaction of laboratory cultivated and commercial algal biomass into crude bio‐oil. Issue 3 (20th April 2017) - Liang, Shaobo; Wei, Liqing; Passero, Maxine L.; Feris, Kevin; McDonald, Armando G.
Abstract : This study investigated the production of crude bio‐oils from three laboratory cultivated and two commercial grade algal biomass sources via hydrothermal liquefaction (HTL) process. Results demonstrated the crude bio‐oils generated from laboratory cultivated algae fed 5% anaerobic digestion effluent as sole nutrient source have similar thermochemical characteristics as comparison with that of derived from commercial algae. The HTL conditions were optimized (300°C for 20 min) and the generated bio‐oils were characterized by gas chromatography mass spectrometry, Fourier transform infrared spectroscopy, and electrospray ionization‐mass spectrometry analyses and simulated distillation by thermogravimetric analysis. The bio‐oil yields were between 28 and 41%. The bio‐oils were mainly comprised of fatty acids and alkanes. These bio‐oils can be further upgraded and refined into value added transportation fuels and chemicals. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 781–787, 2017